Reproductive health needs and the reproductive health behaviour of the youth in Mangaung in the Free State province: a feasibility study - E Seekoe (AOSIS, 2005)
From the community profiles conducted by nursing students in Mangaung, the following observation was prevalent: an increase in the prevalence of teenage pregnancy together with a high prevalence of HIV infection was demonstrated. The relationship between young people's reproductive behavior and the prevalence of HIV is well documented. To address this problem, a community -based education programme is required. Developing a successful community-based educational programme that addresses the needs of youth requires that such a programme be based on the needs of such a group. The research question is applicable: How do youth in Mangaung in the Free State province in South Africa perceive their reproductive health needs and their reproductive health behavior? The aim of this article is to explore and describe the reproductive health needs and the reproductive health behaviour of the youth in Mangaung. A quantitative research design that is descriptive and explorative in nature was conducted. The reproductive health needs and the reproductive health behaviour of the youth were collected by means of a structured questionnaire with open-ended and closed questions. A purposive non - probability sampling method was utilized and (n=250) drawn from the youth. The justification of the sample was further enhanced by collecting data from youth aged 13-25 at three high schools in Mangaung and at the health centre of MUCPP. Qualitative data obtained from open-ended questionnaires was coded and analyzed by using Tech's (1990) content analysis approach. A descriptive statistical analysis was performed on the quantitative data from closed questions. A descriptive analysis of the participant's ages and their perceived reproductive health needs and reproductive health behaviour was done. The mean age of the participants was 18.6, which could be because all the respondents were of school- going age. The results indicated that the youth received insufficient reproductive health information to be able to prevent pregnancy and HIV/AIDS. The special needs of youth were indicated by 92% who requested that the clinic should accommodate both boys and girls and 96% of the respondents requested sessions for discussions facilitated by a professional person. A total of 95% of the youth requested that a special programme of activities be conducted during school holidays. The risk behaviours practised by the youth were: having sex with a stranger, many partners, drinking alcohol, and using drugs and dagga. The researcher recommends that such a programme be supported by different university departments and rolled out to different districts in the Free State province.